Shadow regulation and the shadow banking system - The role of the Dublin International Financial Services Centre - STEWART, JAMES CHARLES (Tax Justice Focus, 2008)
The emerging financial problems in global markets have been described as ?the worst financial crisis since the Great Depression.? The crisis is ongoing, and it is uncertain how deep or protracted it will be.
PUBLISHED
Keywords: Business Studies